An analysis of Zimbabwean hotel managers' perspectives on workforce diversity - Mkono, Muchazondida (Tourism and Hospitality Research, 2021)
Human resource management academics have built a strong case for diversity management, although the concept is not without its flaws. Modern workplaces, and especially hotel workplaces, are characterised by a high degree of diversity: people from different cultural, educational and social backgrounds have to work together towards the achievement of organisational goals. Much of the work on diversity management (DM) has, however, been done in the developed world. With this background in mind, this research set out to analyse Zimbabwean hotel managers' perspectives on workforce diversity, and DM practices in Zimbabwe's hotel industry. Data were collected through an interview survey with 38 human resource managers in 38 hotels located in various towns around Zimbabwe. It was found that most managers accept and tolerate rather than value diversity. The findings also suggest that human resource practices in the industry are still based on the traditional concepts such as Equal Opportunities and Non-discrimination.